Testing overloading in Ecuadorian higher education - Luis Vílchez, Jose (Transformación, 2024)
Objective: The paper aims at proving the inefficiency of administrative imposed overloaded number of assessment exercises in a single semester. This will reduce the time allotted to formative activities. The collected data were also examined in the light of today commercial approach to education.Methods: The quantitative and qualitative outcomes of theoretical and practical evaluation exercises are compared. The students of nine groups of the University of Cuenca were chosen as a sample.Results: In this study, these legal obligations are put into question, proving that one and other types of evaluation measurement are equivalents. This fact empirically invalidates legal normalizations that promote a greater number of evaluations for students’ benefit. The results suggest that there is a significant, positive and moderate correlation of the scores obtained in two types of evaluations: theoretical and practical ones.Conclusions: The author figures out that regardless of the type of technique used poor-performance students will get low grades, while outstanding students will get good marks. The excessive number of evaluation exercises hinders the normal development of teaching and learning in the classroom and the students’ autonomous learning.
Keywords: assessment; skill assessment; educational policies; cognitive development